Exploration of the binding pocket of histone deacetylases: the design of potent and isoform-selective inhibitors - UBA, Abdullahi İbrahim (Turk J Biol, 2017)
Histone deacetylases (HDACs) are enzymes that act on histone proteins to remove the acetyl group and thereby regulate the chromatin state. HDACs act not only on histone protein but also nonhistone proteins that are key players in cellular processes such as the cell cycle, signal transduction, apoptosis, and more. “Classical” HDACs have been shown to be promising targets for anticancer drug design and development. However, the selectivity of HDAC inhibitors for HDAC isoforms remains the motivation of current research in this field. Here, we explored Class I HDACs and HDAC6 by sequence alignment and structural superimposition, catalytic channel extraction, and identification of critical residues involved in HDAC catalysis. Based on the general pharmacophore features of known HDAC inhibitors, we developed a library of compounds by scaffold hopping on a fragment hit identified via structurebased virtual screening of the molecular fragment library retrieved from the Otava database. Molecular docking assay revealed five of these compounds to have increased potency and selectivity for HDACs 1 and 2. Furthermore, their predicted absorption, distribution, metabolism, elimination, and toxicity (ADMET) properties were consistent with those of drug-like compounds. With further modelingbased and experimental investigations, we believe that these findings may offer additional potential HDAC inhibitors with improved selectivity.